Dynamics of finite dimensional non-hermitian systems with indefinite metric - Ramirez, Romina Andrea (2019)
We discuss the time evolution of physical finite dimensional systems which are modelled by non-hermitian Hamiltonians. We address both general non-hermitian Hamiltonians and pseudo-hermitian ones. We apply the theory of Krein Spaces to construct metric operators and well-defined inner products. As an application, we study the stationary behavior of dissipative one axis twisting Hamiltonians. We discuss the effect of decoherence under different coupling schemes.